Ethnocentrism, Trust, and the Willingness to Pay of Chinese Consumers for Organic Labels from Different Countries and Certifiers - Shijiu Yin; Fei Han; Yiqin Wang; Wuyang Hu; Shanshan Lv (Journal of Food Quality)
Although numerous studies have examined consumer preference for organic foods, few have focused on consumer willingness to pay (WTP) for organic labels from dissimilar countries or certifiers. We conducted a choice experiment to examine how Chinese consumer ethnocentrism and trust on organic labels and certifiers may affect their WTP for organic labels from different countries as well as for different certifiers. Chinese consumers did not show a high level of ethnocentrism, and this may lead to inconsistencies in their WTP for organic labels. Significantly, consumer preferences for certifiers did not change remarkably with the increase in consumer ethnocentrism. Chinese consumers generally preferred organic labels from developed countries (or US-invested organic certifiers). With increases in the trust in labels, consumer WTP for each type of organic label increased in general, but the difference between WTPs for organic labels from different countries decreased. Similar results were observed in consumer WTP for certifiers. Determining distinct preferences for organic labels from various sources and countries can be a valuable reference for manufacturers or international certification service providers to choose target markets and for governments to establish their certification systems.